057 Dementia and sociodemographic factors a review. Issue 9 (12th August 2022) - Wu, Kit; Vidot, Micha; Mitchell, James W; Nitkunan, Arani; Carr, Georgina
Abstract : Background: Unwarranted variation in treatment, care and support for people with dementia is well documented. To improve equity of service, in line with the NHS Long Term Plan, it is imperative that we understand how sociodemographic factors affect management and care of dementia. Aim: To review published literature between sociodemographic factors and clinical factors, diagnosis, treatment and outcomes for people with dementia. Method: We conducted a focused review of published literature between 2000-2021 to outline the evidence describing the relationship between the ten protected characteristics of the Equality Act 2010 and clinical factors, treatment and outcomes in dementia. Other factors such as deprivation, settlement status, education and employment were also explored. Results: There is an abundance of published literature on age, race, geographical variation, sex and gender. Evidence is lacking for relationship between disability, gender reassignment, marriage and civil partnership, pregnancy and maternity, religion and belief, sexual orientation, immigration and settlement. Discussion: Better understanding of sociodemographic factors of our patient group is key to improving equity of care. This review has identified gaps in knowledge on factors that may affect how patients access care to dementia services.